Methylmercury Effect and Distribution in Two Extremophile Microalgae Strains Dunaliella salina and Coccomyxa onubensis from Andalusia (Spain) - Simansky, Samuel; Holub, Jiří; Márová, Ivana; Cuaresma, María; Garbayo, Ines; Torronteras, Rafael; Vílchez, Carlos; Gojkovic, Zivan (Microorganisms, 2024)
The main entrance point of highly toxic organic Hg forms, including methylmercury (MeHg), into the aquatic food web is phytoplankton, which is greatly represented by various natural microalgal species. Processes associated with MeHg fate in microalgae cells such as uptake, effects on cells and toxicity, Hg biotransformation, and intracellular stability are detrimental to the process of further biomagnification and, as a consequence, have great importance for human health. The study of MeHg uptake and distribution in cultures of marine halophile Dunaliella salina and freshwater acidophilic alga Coccomyxa onubensis demonstrated that most of the MeHg is imported inside the cell, while cell surface adhesion is insignificant. Almost all MeHg is removed from the culture medium after 72 h. Significant processes in rapid MeHg removal from liquid medium are its abiotic photodegradation and volatilization associated with algal enzymatic activity. The maximum intracellular accumulation for both species was in 80 nM MeHg-exposed cultures after 24 h of exposure for D. salina (from 27 to 34 µg/gDW) and at 48 h for C. onubensis (up to 138 µg/gDW). The different Hg intakes in these two strains could be explained by the lack of a rigid cell wall in D. salina and the higher chemical ability of MeHg to pass through complex cell wall structures in C. onubensis. Electron microscopy studies on the ultrastructure of both strains demonstrated obvious microvacuolization in the form of many very small vacuoles and partial cell membrane disruption in 80 nM MeHg-exposed cultures. Results further showed that Coccomyxa onubensis is a good candidate for MeHg-contaminated water reclamation due to its great robustness at nanomolar concentrations of MeHg coupled with its very high intake and almost complete Hg removal from liquid medium at the MeHg levels tested.
Keywords: microalgae; mercury contamination; mercury toxicity; methylmercury